PERAN PEMERINTAH PROVINSI RIAU DALAM MEMBERIKAN PERLINDUNGAN BAGI TENAGA KESEHATAN PADA MASA PANDEMI COVID-19: The Role Of The Riau Provincial Government In Providing Protection For Health Workers During The Covid-19 Pandemic - Fauzan Raisal Misri; Ninuk Wijiningsih (Faculty of Law, Universitas Trisakti, 2025)
Protection for health workers as the front line in handling Covid-19 is very necessary, the government needs to provide guarantees of occupational protection and safety in efforts to handle Covid-19, Legal certainty plays a crucial role in protecting health workers, ensuring that the government does not act arbitrarily when assigning them to duties.The main problem raised is whether the provisions on the protection of health workers during the Covid-19 pandemic in Riau Province are in accordance with Law Number 36 of 2014 and what are the forms of protection provided by the Riau Provincial Government to health workers on duty. In order to answer these problems, juridical-normative research was carried out based on secondary data and primary data, and Conclusions are drawn using deductive logic. The conclusion from the results of the analysis not in accordance with the process of forming laws and regulations and in the implementation of these rules does not run well because the budget for these incentives is not included in the Regional Expenditure Revenue Budget and it is hoped that in the future the Government must pay attention to the Formation of Governor's Regulations and can be carried out optimally by the relevant agencies.